The Critical Handbook of Money Laundering Policy, Analysis and Myths - van Duyne, Petrus C. (Palgrave Macmillan UK, 2018)
The overarching aim of this book is to bring order to the subjects of money laundering and of the anti-money laundering frameworks that have been written over the past thirty years. It provides scholars, practitioners and policy makers with a guide to what is known of the subject thus far. The book examines critically the underlying assumptions of research and of policy-making in the field and offers a systematic review of the most important policy and academic literature on the subject. .